Mehanizem nastajanja polimerne asimetrične porozne membrane z mokrim postopkom fazne inverzije - Stropnik, Črtomir (Kovine zlitine tehnologije, 1997)
Mechanism of polymeric asymmetric porous membranes prepared by the wet phase inversion process is qualitatively presented. The formation of the morphological characteristic features of membranes from cellulose acetate, polysulfone, poly(methylmetacrylate), thermoplasric polyuretane and polyamide 4,6 is interpreted in terms of the `composition path` in the ternary phase diagram polymer/solvent:nonsolvent and supported by evidences of turbidity phenomena taking place during membrane formation, shrinkage of the cast solution of polymer to the (proto)membrane, and water permeability of membranes.
Keywords: chemistry; kemija; polimeri; membrane; geli; morfologija